(untitled) (Fiep Bulletin - online, 2012)
The National Tuberculosis Control Program of Brazil, in the intention of detecting tuberculosis cases precociously, has as one of its main attributions the active search for symptomatic respiratory in demand of the health services and in community. Once a case is diagnosed, it should be developed the epidemiological investigation among the communicants of patient. The present study aims to analyze the performance of health services in relation to the investigation of communicants of tuberculosis patients in João Pessoa – PB. It is a sectional study, of quantitative approach. The population of this study was formed by tuberculosis patients, and the sample was constituted by 101 patients. The data were collected by means of primary sources (interviews), using as instrument which was validated and adapted to tuberculosis care in Brazil. Moreover, the statistical treatment used bivariate analysis and chi-square association test (2). It was evidenced that most of cases were diagnosed in the Tuberculosis Reference Center, and the demand for symptomatic respiratory at home was accomplished independent of the kind of health service which diagnosed them. In relation to visit patient at home, Primary Care Service presented the highest percentage of coverage, with 94.1%, becoming evident the association between the variables (p=0.0274). There was no association between the variables which analyzed the evaluation of home contacts with sputum examination (p=0.9311), chest X-ray (p=0.3215) and tuberculin skin test (p=0.1007). The results also showed that there was no association between the variables which evaluate if the heath service that diagnosed tuberculosis talked to the home communicants about the disease (p=0.5422) and about their life conditions (p=0.3846). Considering that the quality of actions directed to tuberculosis communicants may facilitate the early diagnosis of disease, and the compromise of health services is fundamental to overcome the fragilities which are still present.